How sleep duration mediated childhood trauma and Internet addiction of the vocational college population in urban areas of south China - Wang, He; Luo, Weijun; Huang, Weikang; Xiang, Haishan; Chen, Siqi; Lin, Wei; Chen, Caiyun; Zhang, Yingjie; Huang, Shengbing; Wang, Yueyun; Liu, Peiyi (Frontiers in Psychiatry, 2023)
Background: Internet Addiction is positively associated with a range of psychological risk factors such as childhood trauma and sleep disorders. However, it remains unclear if sleep duration mediates the association between childhood trauma and Internet addiction. Methods: We enrolled 14263 students from Shenzhen Polytechnic College, China. We assessed sleep duration, Internet addiction and childhood maltreatment in these students by self-report measures, Internet Addiction Test (IAT) and Childhood Trauma Questionnaire (CTQ) respectively. With bootstrap approach and path analysis, we assessed the mediating role of sleep duration in the association between childhood trauma and Internet addiction. Results: The Internet-addicted group exhibited a higher level of the emotional abuse (EA) score, physical abuse (PA) score and sexual abuse (SA) score and a lower level of emotional neglect (EN) score and sleep duration compared with the control group. The CTQ total score and subscores showed a positive correlation with IAT scores both for males and females. The CTQ subcores were negatively related to sleep duration and sleep duration was negatively correlated with IAT scores in both sex groups. Further, the path analysis suggested that EA and SA mediated significantly to the Internet addiction when all types of childhood trauma were examined in one model. Conclusions: In the current study, a great proportion of students met criteria for Internet addiction. Sleep duration mediated a significant proportion of the indirect effect between EA/SA and Internet addiction. The findings may help with prevention and intervention of Internet addiction in the future. The limitation of this study was that it was a cross-sectional study and evaluated one aspect of sleep information. Future large-scale longitudinal studies will be needed to further clarify the relationship between childhood abuse and Internet addiction and the mediation of sleep duration.